Teaching Systems Engineering Practices Using Principles from Studio Art Education. Issue 3 (10th October 2022) - McDermott, Tom; Nadolski, Molly
ABSTRACT: We have created a cross‐disciplinary learning program across studio art, systems thinking, and systems architecture to improve systems competencies. Previous research produced a framework for relating learning concepts across these three domains. We describe how to apply these concepts to any learning situation to increase systems competencies using systems thinking and systems engineering tools. We have applied the framework in educational settings to teach systems thinking, critical thinking, and systems engineering using a tailored classroom approach derived from studio art classes. The studio format encourages the students to build their skills across a portfolio of work focused on creating appropriate views of a system, communicating them, and gaining critical review – three core aspects of the systems thinking process. An effective systems engineer conceptualizes and solves problems, addresses stakeholder concerns, explores and composes solutions, and manages system evolution. The use of art, as embodied in systems‐related tools, has proven to be an effective method for developing these skills. This article presents the framework and an example graduate level Systems and Critical Thinking class taught using the studio art approach.